HRM as a high performance work system for university spin-offs - Sousa, Milton; Barroca, Ana; Flohil, Fleur; Neto, Catarina (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
SPIN-UP Entrepreneurship Training and Coaching Programme was specifically design to meet the needs of management teams in University Spin-Offs. The ultimate goal of the SPIN-UP Training and Coaching Program is the development of Key Entrepreneurial Skills (KES) in University Spin-Offs (USO), enabling/leveraging their growth and allowing for the creation of new knowledge based jobs. The term USO here employed refers to entrepreneurial initiatives often resulting from research and development projects (but not exclusively), led by academic entrepreneurs (professors, teachers and students in High Education Institutions,-HEI). USO can, therefore, be categorized as innovative and knowledge based enterprises. Based on research conducted in 4 European countries–Finland,Poland,Portugaland TheNetherlands-that enabled for the identification of key entrepreneurial skills lacking in University Spin-Offs, the SPIN-UP Entrepreneurship Training and Coaching Programme can act directly on one of the main factors hampering the growth of these kinds of enterprises. SPIN-UP Entrepreneurship Training and Coaching Programme proposes a very practical approach to the learning of entrepreneurial skills, where learning by-doing and other ative learning methodologies, learning with peers and methodologies such as coaching, are blended to provide for a very effective learning experience. By the end of training and coaching sessions, trainees should have improved their abilities in a set of management areas that enable them to face and deal more properly with challenges posed in their enterprises. SPIN-UP training in HRM and Leadership aims to develop in trainees a set of key skills that were found to be essential to enable University Spin-Offs growth. The main objetives are to: know the basics about HRM and Leadership (understand the main concepts around High Performance Work Systems–HPWS - as a model for HRM and understand the model of full range leadership); Identifying HRM and Leadership practices for growth; Developing own HPWS and leadership path for growth.